Method for extracting iron from copper slag through magnetic separation and application of method
By adding calcium oxide-based additives to the copper slag, the control component points are in the C2S primary crystal area, and mineral phase reconstruction and magnetic separation are carried out, which solves the problem of low iron recovery in the existing copper slag iron extraction technology, and achieves efficient iron recovery and energy consumption reduction.
Patent Information
- Application Number
- CN202411691702.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-11
AI Technical Summary
The existing copper slag iron extraction technology has low iron recovery rate and high cost, and the tailings cannot be effectively resourced.
By mixing the copper slag with calcium oxide-based additives, the component points are controlled in the C2S primary crystal region in the CaO-FeO-SiO2 phase diagram, the ore phase is heated to reconstruct, and then slow cooling, crushing and magnetic separation are carried out to obtain magnetite.
It improves the recovery rate and grade of iron in copper slag, reduces the energy consumption in the heating process, extends the life of the electric furnace, and realizes the full quantitative utilization of iron resources in copper slag.
Smart Images

Figure CN119592784A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of copper slag treatment, and in particular relates to a method for magnetic separation of copper slag for iron extraction and application thereof. Background Art
[0002] In the copper production process, an average of 2.2 tons of copper slag is produced for every ton of copper produced. Copper slag is difficult to dispose of, and the accumulated copper slag over the years is conservatively estimated to have exceeded 100 million tons, occupying a large amount of land resources, causing serious secondary pollution of heavy metals and waste of resources. In fact, copper slag is rich in iron, so it is crucial to properly treat copper slag and fully utilize the iron resources in copper slag.
[0003] At present, the commonly used technology for extracting iron from copper slag is to reduce the copper slag into metallic iron phase through reduction. However, there are many impurities in the recovered iron and it is not recognized by the market; the cost of reduction is high and the willingness of factories to accept it is low; there are still a lot of tailings that cannot be recycled. Summary of the invention
[0004] In order to solve the technical problem of low iron recovery rate in the above-mentioned conventional technology of copper slag iron extraction, the present invention provides a method for copper slag magnetic separation iron extraction, comprising the steps of:
[0005] Mixing copper slag and a calcium oxide-based additive to obtain a mixed copper slag, wherein the calcium oxide-based additive includes calcium oxide and / or the calcium oxide raw material, the calcium oxide raw material can generate calcium oxide by heating, and the amount of the calcium oxide-based additive added satisfies: the total mass of the native calcium oxide and / or the generated calcium oxide is 29% to 47% of the mass of the fayalite phase in the copper slag; the calcium oxide raw material includes calcium carbonate and / or calcium sulfate;
[0006] The mixed copper slag is heated to 1250-1800° C. and kept warm for 30-120 minutes to obtain modified copper slag;
[0007] The modified copper slag is subjected to slow cooling, crushing and magnetic separation in sequence to obtain magnetite.
[0008] Furthermore, in the step of slowly cooling, crushing and magnetically separating the modified copper slag to obtain iron, the magnetic field intensity of the magnetic separation is 0.05-0.10T.
[0009] Furthermore, the calcium oxide additive includes calcium oxide. When the calcium oxide-based additive is calcium oxide, the heating temperature is 1400-1800°C; when the calcium oxide-based additive is the calcium oxide raw material, the heating temperature is 1250-1800°C.
[0010] Furthermore, in the step of slowly cooling, crushing and magnetically separating the modified copper slag to obtain iron, the cooling rate of the slow cooling is 0.1-10°C / min.
[0011] Furthermore, when the mass proportion of the crystal stabilizing ions in the copper slag is not greater than 0.5%, the crystal stabilizing ions are added to the copper slag until the mass proportion of the crystal stabilizing ions in the copper slag reaches more than 0.5%, and the ionic polarization ability of the crystal stabilizing ions is less than 4 or greater than 39.
[0012] Further, the crystal stabilizing ions include Na + , K+, Ba 2+ , Sr 2+ , Mn 6+ 、V 5+ Cr 6+ , P 6+ One or more of .
[0013] Furthermore, the modified copper slag comprises magnetite and β-C2S.
[0014] Furthermore, the crushed product is ground, and the particle size of the ground product is not greater than 200 meshes.
[0015] Furthermore, in terms of mass fraction, the mass fraction of the fayalite phase in the copper slag is 10% to 40%.
[0016] The present invention also provides an application of the method for extracting iron from copper slag by magnetic separation as described in any one of the above items in copper slag treatment.
[0017] Compared with the prior art, the present invention has at least the following advantages:
[0018] like Figure 1 As shown, the present invention provides a method for extracting iron from copper slag by magnetic separation, wherein a calcium oxide additive is added to the copper slag, and the calcium content in the calcium oxide additive is limited to 29% to 47% of the mass of the fayalite phase in the copper slag, and the composition point of the copper slag is accurately controlled in the C2S primary crystallization region in the CaO-FeO-SiO2 phase diagram, so that a large amount of C2S is precipitated, and iron is enriched in the form of liquid, which is beneficial to the subsequent crystallization and growth of magnetite crystals, improves the recovery rate and grade of subsequent crushing and magnetic separation of iron, and coordinates the temperature setting of mineral phase reconstruction (after the mixed copper slag is heated to 1250 to 1800°C, the mineral phase reconstruction is achieved in the step of keeping the mixed copper slag warm for 30 to 120 minutes), which greatly reduces energy consumption, is beneficial to extending the life of the electric furnace, and reduces energy consumption during the heating process. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0020] Figure 1 The CaO-FeO-SiO2 phase diagram used in one embodiment of the present invention, wherein the ① region is the FeO primary crystal region, and the ② region is the dicalcium silicate primary crystal region;
[0021] Figure 2 This is a schematic diagram of using calcium oxide as a raw material to generate a dense C2S shell layer, thereby blocking the reaction in an embodiment of the present invention;
[0022] Figure 3 The figure is a schematic diagram of the process of magnetic separation of copper slag for iron extraction in one embodiment of the present invention. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0025] When numerical ranges are given in the embodiments, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any method, device and material of the prior art similar or equivalent to the method, device and material in the embodiments of the present invention can also be used to implement the present invention.
[0026] In common technologies, the composition points of copper slag after adjustment are mostly concentrated in the primary crystal region of FeO in the CaO-FeO-SiO2 phase diagram, such as Figure 1 As shown in area ① in the figure, the liquidus content of iron in the primary crystal area is relatively low, and most of the iron will still precipitate in the form of pyroxene together with calcium, silicon and oxygen, reducing the iron recovery rate.
[0027] In comparison, the present invention controls the composition point in the copper slag in the C2S primary crystallization zone in the CaO-FeO-SiO2 phase diagram by adjusting the amount of calcium oxide-based additives added, so that the liquidus iron content reaches more than 90%, and the iron element is enriched in the mother liquor, which step-wise optimizes the recovery effect of the iron element and minimizes iron loss.
[0028] Based on the above effects, Figure 3 As shown, the present invention provides a method for extracting iron from copper slag by magnetic separation, comprising the steps of:
[0029] S1. Mixing copper slag and a calcium oxide-based additive to obtain a mixed copper slag, wherein the calcium oxide-based additive includes calcium oxide and / or the calcium oxide raw material, the calcium oxide raw material can generate calcium oxide by heating, and the amount of the calcium oxide-based additive added satisfies: the total mass of the native calcium oxide and / or the generated calcium oxide is 29% to 47% of the mass of the fayalite in the copper slag; the calcium oxide raw material includes calcium carbonate and / or calcium sulfate;
[0030] The native calcium oxide is the calcium oxide included in the calcium oxide-based additive, and the generated calcium oxide is the calcium oxide that can be generated by heating the calcium oxide raw material.
[0031] Herein, heating generation refers to that the calcium oxide raw material is heated to a certain temperature to release carbon dioxide and / or sulfur dioxide to generate calcium oxide.
[0032] Exemplarily, the total mass of native calcium oxide and / or generated calcium oxide can be 30% to 35% of the mass of the copper slag, such as 36% to 40%, 40% to 47%; in some specific embodiments, the total mass of native calcium oxide and / or generated calcium oxide can be 30% to 35% of the mass of fayalite in the copper slag; in some more specific embodiments, the total mass of native calcium oxide and / or generated calcium oxide can be 40% to 47% of the mass of fayalite in the copper slag.
[0033] The copper slag may be copper smelting slag or copper tailings slag. In some embodiments, the composition of the copper slag includes 10% to 40% by weight of a fayalite phase.
[0034] In some embodiments, the calcium oxide additive includes calcium oxide, calcium carbonate, and / or calcium sulfate.
[0035] In some embodiments, when the concentration of the crystal stabilizing ions in the copper slag is not greater than 0.5%, the crystal stabilizing ions can be added to the copper slag until the mass proportion of the crystal stabilizing ions in the copper slag reaches more than 0.5%, and the ionic polarization ability of the crystal stabilizing ions is less than 4 or greater than 39.
[0036] The crystal stabilizing ions include Na +, K+, Ba 2+ , Sr 2+ , Mn 6+ 、V 5+ Cr 6+ , P 6+ One or more of .
[0037] After the addition of crystalline ions, the crystal transformation of β-dicalcium silicate → γ-dicalcium silicate during the slow cooling process can be effectively inhibited. β-dicalcium silicate can be used as a cement material in the cement industry, realizing the full quantitative recycling of copper slag.
[0038] Among them, the ion polarization ability is the attraction or repulsion of the electric field generated by the charged ion on the electron cloud of another ion. The test method can be used C 2 / R represents (C – charge, R – ionic radius).
[0039] S2. After heating the mixed copper slag to 1250-1800° C., keep the temperature for 30-120 minutes to obtain modified copper slag.
[0040] During the process in step S2, the mixed copper slag is subjected to mineral phase reconstruction at high temperature to obtain modified copper slag.
[0041] During the mineral phase reconstruction process, the reaction between calcium oxide and silicon dioxide in the copper slag effectively destroys the fayalite phase, promotes the transformation of the fayalite phase in the slag, and promotes the formation of magnetite to obtain the magnetite phase and β-C2S. In the subsequent cooling and crystallization process, the components in the copper slag can be more fully mixed and diffused, and sufficient insulation time can ensure that the components in the copper slag have enough time to react and reconstruct, thereby forming stable crystals.
[0042] like Figure 1 As shown, the present invention provides a method for extracting iron from copper slag by settling, wherein a calcium oxide additive is added to the copper slag, and the calcium content in the calcium oxide additive is limited to 29% to 47% of the mass of the fayalite phase in the copper slag, and the composition point of the copper slag is precisely controlled in the C2S primary crystallization zone in the CaO-FeO-SiO2 phase diagram, so that the iron content of the liquidus is more than 90%, and the temperature setting of the ore phase reconstruction is coordinated to enrich the iron element in the liquid phase, thereby achieving a significant increase in the recovery rate of iron resources in the copper slag from the source.
[0043] However, the applicant found that Figure 2 As shown, when the composition point of copper slag is controlled in the C2S primary crystallization zone, the mixed copper slag of this composition will form a dense high-melting-point dicalcium silicate shell layer during the mineral phase reconstruction process, which will cover the surface of calcium oxide and inhibit the reaction process.
[0044] In view of this, when the calcium oxide additive is calcium carbonate and / or calcium sulfate, the temperature of mineral phase reconstruction can be 1250-1400°C, because:
[0045] CaCO3→CaO+CO2 (the CO2 produced by the reaction can break the dense C2S shell and reduce the reaction temperature, otherwise the shell needs to be dissolved by heating)
[0046] CaSO4→CaO+SO2 (SO2 produced by the reaction can break up the dense C2S shell and reduce the reaction temperature, otherwise the shell needs to be dissolved by increasing the temperature)
[0047] In some embodiments, when the calcium oxide additive is calcium carbonate and / or calcium sulfate, the temperature of mineral phase reconstruction may be 1250-1400°C.
[0048] Calcium carbonate and calcium sulfate absorb heat and decompose in a high temperature environment. The generated carbon dioxide or sulfur dioxide gas can destroy the dicalcium silicate shell, fully exposing calcium oxide, and the reaction between calcium oxide and silicon dioxide can proceed.
[0049] For example, when the calcium oxide additive is calcium carbonate and / or calcium sulfate, the temperature of mineral phase reconstruction may be 1250-1800°C.
[0050] When the calcium oxide-based additive is calcium oxide, the temperature of mineral phase reconstruction can be adjusted to 1400-1800°C. The dicalcium silicate shell melts at this temperature, which ensures the full reaction of calcium oxide and silicon dioxide while providing the necessary energy and kinetic conditions for the subsequent precipitation and crystallization of β-dicalcium silicate.
[0051] The present invention achieves stable optimization of iron recovery rate by synergistically adjusting the type of calcium oxide-based additives and the temperature of mineral phase reconstruction. In comparison, in the conventional technology, only monocalcium silicate will be generated in the copper slag falling into the FeO primary crystallization zone. The density of monocalcium silicate is low and it will not form a dense shell. Therefore, it will not face the technical problem of dicalcium silicate shell coating in the present application, and there is no motivation to adjust the type of calcium oxide-based additives and the temperature of mineral phase reconstruction.
[0052] S3. The modified copper slag is sequentially subjected to slow cooling, crushing, grinding and magnetic separation to obtain iron.
[0053] Based on the aforementioned regulation of the composition point of the mixed copper slag, the composition point of the mixed copper slag is located in the primary crystallization zone of dicalcium silicate. During the slow cooling process, dicalcium silicate is preferentially precipitated, and the liquidus iron content is controlled to be above 90%. During the slow cooling process, the copper mineral particles aggregate and grow, and the monomer dissociation degree of magnetite is significantly improved, which is conducive to the effective separation of magnetite in the subsequent magnetic separation process, and further improves the iron recovery rate.
[0054] In some embodiments, the slow cooling has a cooling rate of 0.1 to 10°C / min; in some specific embodiments, the slow cooling has a cooling rate of 0.1 to 1°C / min; in some more specific embodiments, the slow cooling has a cooling rate of 0.1 to 0.25°C / min.
[0055] The particle size of the product after crushing and grinding is not greater than 200 mesh.
[0056] The magnetic field strength during the magnetic separation process can be 0.05-0.10T.
[0057] The present invention provides an application of the method for extracting iron from copper slag by magnetic separation as described in any one of the above items in copper slag treatment.
[0058] In order to facilitate those skilled in the art to further understand the present invention, examples are given below:
[0059] Example 1
[0060] A method for extracting iron from copper slag by magnetic separation, comprising the following steps:
[0061] A copper smelting slag was selected for chemical phase analysis, and the mass content of iron olivine in the copper smelting slag was determined to be 16.5%, the mass content of magnetite was 18.4%, and the total iron content was 39.8%; the copper slag carried the crystal stabilizer Na2S. + , the content is 1.53%.
[0062] A CaO-based additive is added to the copper smelting slag to obtain a mixed copper slag. The calcium oxide-based additive is CaCO3, and the amount of CaCO3 added is 12% of the mass of the copper slag, that is, the calcium oxide content in the calcium carbonate is equivalent to 40.7% of the mass of the fayalite.
[0063] The mixed copper slag is heated to 1450°C and kept warm for 60 minutes to obtain modified copper slag; the modified copper slag comprises magnetite and β-C2S.
[0064] The modified copper slag is slowly cooled at a rate of 0.5°C / min. During the slow cooling process, the magnetite grains grow. The slowly cooled copper slag is crushed and ground. The particles after grinding can pass through a 200-mesh sieve. The ground product is magnetically separated at an intensity of 0.07T.
[0065] After mineral phase reconstruction, chemical phase analysis of the copper slag showed that the magnetite content was 35%, and the iron grade of the magnetite obtained after magnetic separation was 61.2%, which can enter the pre-iron system. The remaining tailings are β-C2S, which can enter the cement industry.
[0066] Example 2
[0067] A method for extracting iron from copper slag by magnetic separation, comprising the following steps:
[0068] A copper tailings slag was selected for chemical phase analysis, and the mass content of fayalite, magnetite and total iron in the copper smelting slag was determined to be 18.5%, 25.4% and 46.8% respectively; the amount of crystal stabilizing ions in the copper smelting slag did not exceed 1%, and a crystal stabilizer Ca3(PO4)2 was added thereto, the mass of which was 2% of the mass of the copper slag;
[0069] A CaO-based additive is added to the copper smelting slag to obtain a mixed copper slag. CaO is selected, and the addition amount of CaO is 7% of the mass of the copper slag, that is, the addition amount of calcium oxide is equivalent to 37.8% of the mass of fayalite.
[0070] The mixed copper slag is heated to 1750°C and kept warm for 90 minutes to obtain modified copper slag, wherein the modified copper slag comprises magnetite and β-C2S;
[0071] The modified copper slag is slowly cooled at a rate of 1°C / min, and magnetite grains grow during the slow cooling process. The copper slag after slow cooling is crushed and ground, and the particles after grinding can be passed through a 350-mesh screen to perform magnetic separation on the grinding product, and the magnetic separation intensity is 0.06T.
[0072] After mineral phase reconstruction, chemical phase analysis of the copper slag showed that the magnetite content was 43.2%, and the iron grade of the magnetite obtained after magnetic separation was 63.1%, which can enter the pre-iron system. The remaining tailings are β-C2S, which can enter the cement industry.
[0073] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for extracting iron from copper slag by magnetic separation, characterized in that: Includes steps: Mixing copper slag and a calcium oxide-based additive to obtain a mixed copper slag, wherein the calcium oxide-based additive includes calcium oxide and / or the calcium oxide raw material, the calcium oxide raw material can generate calcium oxide by heating, and the amount of the calcium oxide-based additive added satisfies: the total mass of the native calcium oxide and / or the generated calcium oxide is 29% to 47% of the mass of the fayalite phase in the copper slag; the calcium oxide raw material includes calcium carbonate and / or calcium sulfate; The mixed copper slag is heated to 1250-1800° C. and kept warm for 30-120 minutes to obtain modified copper slag; The modified copper slag is subjected to slow cooling, crushing and magnetic separation in sequence to obtain magnetite.
2. The method for extracting iron from copper slag by magnetic separation according to claim 1, characterized in that: In the step of slowly cooling, crushing and magnetically separating the modified copper slag in sequence to obtain iron, the magnetic field intensity of the magnetic separation is 0.05-0.10T.
3. The method for extracting iron from copper slag by magnetic separation according to claim 1, characterized in that: The calcium oxide additive includes calcium oxide. When the calcium oxide-based additive is calcium oxide, the heating temperature is 1400-1800°C; when the calcium oxide-based additive is the calcium oxide raw material, the heating temperature is 1250-1800°C.
4. The method for extracting iron from copper slag by magnetic separation according to claim 1, characterized in that: In the step of slowly cooling, crushing and magnetically separating the modified copper slag to obtain iron, the cooling rate of the slow cooling is 0.1-10°C / min.
5. The method for extracting iron from copper slag by magnetic separation according to claim 1, characterized in that: When the mass proportion of the crystal stabilizing ions in the copper slag is not more than 0.5%, the crystal stabilizing ions are added to the copper slag until the mass proportion of the crystal stabilizing ions in the copper slag reaches more than 0.5%, and the ion polarization ability of the crystal stabilizing ions is less than 4 or greater than 39.
6. The method for extracting iron from copper slag by magnetic separation according to claim 5, characterized in that: The crystal stabilizing ions include Na + , K+, Ba 2+ , Sr 2+ , Mn 6+ 、V 5+ Cr 6+ , P 6+ One or more of .
7. The method for extracting iron from copper slag by magnetic separation according to claim 6, characterized in that: The modified copper slag comprises magnetite and β-C2S.
8. The method for extracting iron from copper slag by magnetic separation according to claim 1, characterized in that: The crushed product is ground, and the particle size of the ground product is not greater than 200 meshes.
9. The method for extracting iron from copper slag by magnetic separation according to claim 1, characterized in that: In terms of mass fraction, the mass fraction of the fayalite phase in the copper slag is 10% to 40%.
10. Use of the method for magnetic separation of iron from copper slag as claimed in any one of claims 1 to 9 in copper slag treatment.
Citation Information
Cited By
Method for reconstructing slow cooling copper slag ore phase coupling thermal-mass circulation through limestone-FeS-carbon powder
CN120733866A
Method for efficiently extracting iron from copper slag through non-molten hydrogen reduction
CN121109739A